E-Participation in smart cities. Technologies and models of governance for citizen engagement. - (:unkn) unknown (Springer International Publishing, 2019)
This book analyzes e-participation in smart cities. In recent decades, information and communication technologies (ICT) have played a key role in the democratic political and governance process by allowing easier interaction between governments and citizens, and the increased ability of citizens to participate in the production chain of public services. E-participation plays an important role in the development of smart cities and smart communities, but it has not yet been extensively studied. This book fills that gap by combining empirical and theoretical research to analyze actual practices of citizen involvement in smart cities and build a solid framework for successful e-participation in smart cities.
Keywords: Stadt; Verwaltung; Informationstechnologie; Partizipation; Selbstverwaltung; Mitwirkung; Kooperation; Öffentliche Aufgabe; E-Partizipation; Urban Governance; Bürgerbeteiligung; Institutionalisierung; Open Government; Stadtverwaltung; Stadtmanagement; Smart City